A IMPROVING MOTIVATION, PERCEPTION AND PREFERENCES OF LEARNING MATHEMATICS THROUGH ANCIENT METHODS / TECHNIQUES - Tri E, S (Jurnal Dimensi Matematika, 2020)
This study aims to examine the increase in motivation, perception, and preferences for mathematics education through ancient methods or techniques. In this study, the approach used is quantitative by using non-parametric statistical tests, namely: Hypothesis testing on signs, hypothesis testing through the Wilcoxon Signed level, and hypothesis testing for changes. The conclusion from this research is that the experiment is in the form of giving treatment or stimulating mathematics learning through ancient methods or techniques in the form of: Addition of Many Numbers with the Ladder of Wisdom, Easy Subtraction with the Nine Yin Yang Technique, Easy Multiplication with Napier's Bones, and Easy Division using the Chunking Method (Chunk It). ): 1) able to increase motivation in mathematics learning based on hypothesis testing on signs, 2) able to change the perception that learning mathematics is easy and fun based on testing the Hypothesis through the Wilcoxon Marked Level, and 3) able to change preferences to become students who are diligent in learning mathematics based on testing hypotheses for change.